Determinasi Sosio-ekonomi terhadap Keputusan Perempuan Bekerja di Sektor Informal Desa Lendang Belo, Lombok Timur - Musniasih Yuniati; Yorman Yorman; Meiyanti Widyaningrum; Desi Suryati; Rohimatun Rohimatun (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the factors that influence women's decisions to work in the informal sector in Lendang Belo Village, East Lombok Regency. The method used is a quantitative approach with binary logistic regression analysis techniques on 33 adult female respondents. The results of the study indicate that of the four independent variables analyzed, namely age, number of family dependents, education level, and household income, three of them have a significant effect on women's decisions to work in the informal sector, namely the number of dependents (p = 0.030), education level (p = 0.045), and income (p = 0.039). Meanwhile, the age variable does not have a significant effect (p = 0.119). The logistic regression model used is proven to be statistically feasible (Hosmer and Lemeshow test: p = 0.733; Nagelkerke R² = 0.655) and has a predictive accuracy level of 81.8%. These findings indicate that household economic pressures are the main driver of women's participation in the informal sector, while age is not a determining factor in this context. This study provides the importance of the formulation of women's empowerment policies based on rural contextual.